2016
DOI: 10.1016/j.elecom.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

A highly-concentrated poly(ethylene carbonate)-based electrolyte for all-solid-state Li battery working at room temperature

Abstract: We report an all-solid-state Li rechargeable battery based on a hybrid membrane comprising a highly-concentrated poly(ethylene carbonate) (PEC) electrolyte with 80 wt% of lithium bis(fluorosulfonyl)imide (LiFSI) and a three-dimensionally ordered macroporous polyimide matrix operating at room temperature. The PEC-LiFSI 80 wt% electrolyte showed an ionic conductivity of the order of 10 -5 S cm -1 at 30 o C and quite high Li transference number, and was employed as a good ion-conductive solid polymer membrane for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 22 publications
2
121
1
Order By: Relevance
“…2(b) presented the temperature dependence of ionic conductivity for PDEC-LiTFSI and PTEC-LiTFSI electrolytes. It could be observed that the temperature dependence agreed well with the Arrhenius equation over the range of C. These electrolytes behaved like the poly(ethylene carbonate) based electrolytes due to similar chemical structures, which was in good accordance with the previous reports by Tominaga [46,47]. The ionic conductivity of PDEC-LiTFSI was 3.81 Â10 À6 S cm À1 at 25 C and 8.11 Â10 À5 S cm À1 at 80 C, respectively.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…2(b) presented the temperature dependence of ionic conductivity for PDEC-LiTFSI and PTEC-LiTFSI electrolytes. It could be observed that the temperature dependence agreed well with the Arrhenius equation over the range of C. These electrolytes behaved like the poly(ethylene carbonate) based electrolytes due to similar chemical structures, which was in good accordance with the previous reports by Tominaga [46,47]. The ionic conductivity of PDEC-LiTFSI was 3.81 Â10 À6 S cm À1 at 25 C and 8.11 Â10 À5 S cm À1 at 80 C, respectively.…”
Section: Resultssupporting
confidence: 78%
“…These results were much superior to the PEO based lithium batteries [60] and comparable to the PEC and P (CL-co-TMC) based lithium batteries [46,47,49]. The rate capability of the Li/LiFePO 4 cell from 0.1C to 0.5C at 55 C is presented in Fig.…”
Section: à2mentioning
confidence: 61%
See 2 more Smart Citations
“…Adjusting lithium‐salt concentration can also improve the lithium conduction of PEC solid polymer electrolyte. Tominaga reported macroporous polyimide‐supported PEC/LiFSI (in which, the weight ratio of LiFSI to PEC was 4:1). The conductivity reached 1.6 × 10 −5 S cm −1 at 30 °C.…”
Section: Pec‐spesmentioning
confidence: 99%